2015
DOI: 10.1111/mve.12143
|View full text |Cite
|
Sign up to set email alerts
|

Swarming and mating activity of Anopheles gambiae mosquitoes in semi‐field enclosures

Abstract: Anopheles gambiae Giles sensu stricto (Diptera: Culicidae) is the major Afro-tropical vector of malaria. Novel strategies proposed for the elimination and eradication of this mosquito vector are based on the use of genetic approaches, such as the sterile insect technique (SIT). These approaches rely on the ability of released males to mate with wild females, and depend on the application of effective protocols to assess the swarming and mating behaviours of laboratory-reared insects prior to their release. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…However, it is difficult to compare such characteristics between semi-field and field as the semi-field population is finite and because the marker size could play a role in swarm size [31]. As in Achinko et al [21], time at which mosquitoes started to swarm in the MERF was also consistent across days and was not different than time recorded in the field at the same period by Sawadogo et al [19] (18:43 h in August).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is difficult to compare such characteristics between semi-field and field as the semi-field population is finite and because the marker size could play a role in swarm size [31]. As in Achinko et al [21], time at which mosquitoes started to swarm in the MERF was also consistent across days and was not different than time recorded in the field at the same period by Sawadogo et al [19] (18:43 h in August).…”
Section: Discussionmentioning
confidence: 99%
“…Although field experiments have been attempted by manipulating swarm markers [8, 14], it is difficult to control for environmental and mosquito parameters that lead to swarm formation in the field, which makes the interpretation of results questionable and restricts progress in our understanding of mating behavior. With this in mind, setups have been built and have shown that Anopheles species were able to produce swarms, mate and reproduce in semi-field setups [2124]; however, tools specially designed for experimental swarming behavior studies are needed. Such tools need to provide conditions allowing to trigger swarming behavior but also should allow to control for visual parameters used by mosquitoes to locate their swarms (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, B2T-mBax males appeared to have competitiveness with wild-type males in mating. Since mosquitoes were forced to mate in small cages in this study, further analysis in mass-mating in large spaces would be required for defining the competitiveness of transgenic line males to mate with females in the wild 36,37 .…”
Section: Discussionmentioning
confidence: 99%
“…Acoustic signals play an important role in mate selection, but the role of pheromones is less clear and only explored for Aedes aegypti [ 51 ]. Mating behaviour receives increased attention as a result of the proposed releases of sterile insects (SIT) through irradiation or genetic engineering whereby mate finding and competition are crucial for rapid spread in wild populations [ 52 56 ]. Furthermore, successful implementation of SIT requires a large production of sterile males for which insights in mating behaviour can be used to optimize rearing conditions and boost mosquito colonies [ 57 , 58 ].…”
Section: Behaviour Across the Mosquito Life Historymentioning
confidence: 99%